2015
DOI: 10.5539/ep.v4n3p27
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Solid Waste Management in the Bolgatanga Municipality of the Upper East Region, Ghana

Abstract: Management of domestic solid waste is one of the challenges facing many metropolitan municipal and district Assemblies in Ghana because uncollected and improperly disposed waste results in the clogging of most public areas, streets, and gutters and has a grave implications on health. In the Bolgatanga municipality, as a result of increasing urban population, a high consumption and disposal lifestyle that has no need for reuse, negative attitude by individuals and households in the handling of waste and the ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
(2 reference statements)
1
10
0
1
Order By: Relevance
“…This finding indicates as population increase, the solid waste generations also increase. In accordance with the present results, previous study also has demonstrated that there was strong positive correlation between population and quantity of solid waste produced [12]. Besides, positive strong correlation was established between household income and solid waste generation (r=0.96, p<0.05).…”
Section: Resultssupporting
confidence: 92%
“…This finding indicates as population increase, the solid waste generations also increase. In accordance with the present results, previous study also has demonstrated that there was strong positive correlation between population and quantity of solid waste produced [12]. Besides, positive strong correlation was established between household income and solid waste generation (r=0.96, p<0.05).…”
Section: Resultssupporting
confidence: 92%
“…One of the reasons for the high population density is the high fertility rate of 4.7 and immigration from deprived districts across the region. Apart from these, the peaceful environment characterizing the Bolgatanga Municipality coupled with its relatively endowed natural resources, especially at its periphery, as well as its commerce-oriented economy has acted as a trigger for migrants from Bawku because of the chieftaincy and related conflicts (Ampofo et al, 2015). Figure 1 is used to indicate the geographical location of Bolgatanga as the study area and situated within the regional contextualization of the Upper East Region.…”
Section: Study Area Description-location Land Tenure Systems and Urba...mentioning
confidence: 99%
“…These areas, which include Tindomoligo, Yikene, Yarigabisi, and Tindonsobligo among others, offer cheaper land for housing development for the increasing urban population and for other complementary urban activity as well. The rapid urban growth is attributed to natural population growth and migration from rural areas due to poverty and land conflicts (Ampofo et al, 2015). The Bolgatanga Muncipality has experienced a rapid urban land expansion over the past 30 years; it increased by 6 times; from 499.49 hectares in 1984 to 1525.14 hectares in 2016 with an annual growth rate of 6.4%.…”
Section: Trends and Extent Of Peri-urbanizationmentioning
confidence: 99%
“…For liquid waste disposal, that is throwing waste onto the streets (64.7%) and onto the compound (10.9%) are the two most common methods used by households in most Municipalities in Ghana. A study by [35] titled "Investigating Solid Waste Management in the Bolgatanga Municipality of the Upper East Region, Ghana", revealed that, the most predominant waste disposal is the communal disposal at sites normally not approved in the peri-urban communities. This was followed by the door-to-door services which was prevalent in the urban residential areas.…”
Section: Introductionmentioning
confidence: 99%
“…The municipality like many other local government areas is suffocating in generated waste. Though a number of studies have been undertaken to assess diverse perspectives of waste in the municipality [35], [57][58], much attention has not been devoted in identifying the militating factors to proper waste management in the municipality. A study by [59] indicated that, volumes of solid waste in towns will run into millions of tons and would accumulate if no proper management schemes are put in place to collect them.…”
Section: Introductionmentioning
confidence: 99%